Comparison of Antimicrobial Consumption Patterns in the Swiss and Danish Cattle and Swine Production (2007–2013) - Carmo, Luís P.; Nielsen, Liza R.; Alban, Lis; Müntener, Cedric R.; Schüpbach-Regula, Gertraud; Magouras, Ioannis (Frontiers in Veterinary Science, 2017)
Veterinary antimicrobial consumption patterns vary considerably across Europe. These differences are not only limited to the total amount consumed, but are also observed with regards to the relative proportion of the various antimicrobial classes used. Currently, most of the data on veterinary antimicrobials are reported at sales level without any information on the consumption by different animal species. This hinders a proper comparison of antimicrobial consumption at the species level between countries. However, it is imperative to improve our understanding on antimicrobial usage patterns at the species level, as well as on the drivers contributing to those differences. This will allow for development of tailored interventions with the lowest possible risk for human health, while ensuring effective treatment of diseased livestock. An important step to attain such an objective is to perform detailed comparisons of the antimicrobial consumption in each species between countries. We compared antimicrobial consumption estimates for cattle and pigs in Switzerland and Denmark, in order to distinguish species-specific patterns and trends in consumption from 2007 to 2013. Swiss data were obtained from a previous study that assessed methodologies to stratify antimicrobial sales per species; Danish antimicrobial consumption estimates were assembled from DANMAP reports. A decrease in antimicrobial consumption in mg per kg of biomass was observed for both countries (4.5% in Denmark and 34.7% in Switzerland) when comparing 2013 to 2007. For pigs and cattle, the overall consumption per kg of biomass of most antimicrobial classes was higher in Switzerland than in Denmark. Large variations in the relative consumption of different antimicrobial classes were also evident. Sulfonamides/ trimethoprim and tetracyclines were consumed in a higher proportion in Switzerland than in Denmark, whereas the relative consumption of penicillins was higher in Denmark. The differences observed in veterinary antimicrobial consumption are not solely related to animal demographic characteristics in these two countries. Other factors, such as the level of biosecurity and farming practices, veterinarians and farmers’ education or governmental/industry programs put in place might also partly explain these variations. These differences should be taken into account when aiming to implement targeted interventions to reduce antimicrobial consumption.